The infuence of diferent downstream plate length towards the fow‑induced vibration on a square cylinder - Nurshafnaz Mohd Maruai, Nurshafnaz Mohd Maruai; Mohamed Sukri MatAli, Mohamed Sukri MatAli; SheikhAhmad Zaki, SheikhAhmad Zaki; JorgeAlfredoArdila‑Rey, JorgeAlfredoArdila‑Rey; IzuanAmin Ishak, IzuanAmin Ishak (2023)
The investigations of fow-induced vibration have been around for decades to solve many engineering problems related to structural element. In a hindsight of advancing technology of microelectronics devices, the implementation of fow-induced vibration for energy harvesting is intrigued. The infuence of downstream fat plate to fow-induced vibration experienced by a square cylinder is discussed in this study to surpass the limitation of wind energy due to geographical constraints and climate change. The mechanism of fow-induced vibration experienced by a square cylinder with downstream fat plate is numerically simulated based on the unsteady Reynolds Navier–Stokes (URANS) fow feld. The Reynolds number, Re assigned in this study is ranging between 4.2 × 103 –10.7 × 103 and the mass damping ratio designated for the square cylinder is m∗ζ = 2.48. The infuence of three diferent fat plate lengths w/D = 0.5, 1 and 3 is examined. Each case of diferent fat plate is explored for gap separation between the square cylinder and the plate in the range 0.5 G/D 3. Based on the numerical fndings, the confguration of cylinder-fat plate with length w/D = 1 has shown the highest potential to harvest high energy at comparatively low reduced velocity.